Modern Aspects of English Language Teaching - Ergashevna, Kultaeva Feruza (Innovative: International Multidisciplinary Journal of Applied Technology (2995-486X), 2024)
As methodological and psychological-pedagogical studies show, the use of role-playing communicative games opens up wide opportunities for activating and optimizing the educational process, which is an important means of organizing pair and group work. The motivation for mastering a foreign language, first of all, is the professional need of a student who is preparing to become a highly qualified specialist with knowledge of a foreign language. Therefore, one of the main features of a foreign language in non-linguistic universities should be its professionally oriented nature, reflected in the educational goal and content of education.